Analysıs Of Parental Support To Reduce Student Learning Insecure Durıng The Covıd-19 Pandemic - Hartinah, Hartinah; Putra, Andi Riswandi Buana; Nurrohman, Heru; Setiawan, Muhammad Andi (International Journal of Universal Education, 2023)
Parental support to reduce learning insecurity is very important so that self-confidence and security in children can increase. This study aims to determine parental support to reduce student learning insecurity during the COVID-19 pandemic. Insecure is more experienced by students with a quiet and quiet character. The emergence of a lack of confidence, shame, anxiety, and insecurity makes students less comfortable when studying at school and at home. In addition, students who experience this make them students who are less active, less creative, and dare not express their opinions or ideas when learning takes place, so there needs to be motivation given from parents to children when studying at home, especially during the Covid-19 pandemic where the school holds an online learning program that requires parents to be more active in paying attention to children while learning. Parents must provide more support to reduce the insecurity that grows in children, especially lack of confidence and shame so that they can Cause excessive feelings of anxiety and trigger feelings of insecurity when socializing at school.